EFFICACY OF HYPERBARIC OXYGEN THERAPY MONITORED BY FLUORESCEIN ANGIOGRAPHY IN PATIENTS WITH RETINAL ARTERY OCCLUSION - SHAHZAIB, M; INAM, N; AWAN , AH; AHMED, S; SABIR, N; ALI, B; IQBAL, MZ; NAEEM, M (Biological and Clinical Sciences Research Journal, 2024)
: Retinal artery occlusion (RAO) is a critical ophthalmic condition, often likened to a stroke of the eye, due to its sudden onset and the severe, potentially permanent loss of vision it can cause. Objectives: The study’s main objective is to find the efficacy of hyperbaric oxygen therapy monitored by fluorescein angiography in patients with retinal artery occlusion. Methods: This prospective observational study was conducted at Shalamar Hospital, Lahore, from August 2023 to February 2024. Data were collected from 85 patients. Patients were recruited from the ophthalmology department. Patients aged > 18 years who presented with acute RAO, defined by sudden visual loss and confirmed by clinical examination and initial FA. Both CRAO and BRAO cases were included, provided that the onset of symptoms occurred within 24 hours before presentation were included in the study. Results: The study involved 85 patients aged 45 to 78 years and a mean age of 55.67 years. The gender distribution was predominantly male (61%), with 52 males and 33 females (39%). Among the patients, 59% had Central Retinal Artery Occlusion (CRAO), while 41% had Branch Retinal Artery Occlusion (BRAO). The average time to initiate Hyperbaric Oxygen Therapy (HBOT) was 10 hours, ranging from 4 to 22 hours. At baseline, the mean Best Corrected Visual Acuity (BCVA) was 20/200, with no patients achieving a BCVA of 20/60 or better. After the initial HBOT, the mean BCVA improved to 20/160, with 10% of patients reaching 20/60 or better. At the 24-hour follow-up, BCVA further enhanced to 20/120, with 25% of patients achieving 20/60 or better. Conclusion: It is concluded that hyperbaric oxygen therapy (HBOT) can significantly improve retinal perfusion and visual acuity in patients with retinal artery occlusion, particularly when initiated within 10 hours of symptom onset.